Dendritic Cell Metabolism and Function in Tumors. Issue 8 (August 2019) - Giovanelli, Paolo; Sandoval, Tito A.; Cubillos-Ruiz, Juan R.
Abstract : Dendritic cells (DCs) are fundamental for the initiation and maintenance of immune responses against malignant cells. Despite the unique potential of DCs to elicit robust anticancer immunity, the tumor microenvironment poses a variety of challenges that hinder competent DC function and consequently inhibit the development of protective immune responses. Here, we discuss recent studies uncovering new molecular pathways and metabolic programs that tumors manipulate in DCs to disturb their homeostasis and evade immune control. We also examine certain state-of-the-art strategies that seek to improve DC function and elicit antitumor responses in hosts with cancer. Understanding and modulating DC metabolism and activity within tumors might help improve the efficacy of T cell-centric immunotherapies. Highlights: Tumors can disrupt normal DC functions to evade immune control. Adverse conditions and factors in the tumor milieu modulate specific transcriptional programs and metabolic processes in infiltrating DCs to inhibit their immunogenic activity. Cancer-associated DCs with altered mitochondrial and lipid metabolism demonstrate reduced capacity to elicit T cell-based responses against tumors. Targeting metabolic pathways in intratumoral DCs might be used to elicit durable anticancer immunity and enhance the efficacy of T cell-based immunotherapies.